2012
DOI: 10.1111/j.1748-3743.2012.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguities: residents’ experience of ‘nursing home as my home’

Abstract: Ambiguities concerning the nursing home as a home and place to live, a social environment in which the residents experience most of their social life and the institution where professional health service is provided were uncovered. High-quality care was when ambiguities were managed well and a home could be created within the institution. Implication for practice. Achieving quality care in nursing homes requires reconciling the ambiguities of the nursing home as a home. This implies helping residents to create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(115 citation statements)
references
References 25 publications
3
111
0
1
Order By: Relevance
“…Activities that are regarded as private do not always occur away from other people's gaze (Solove, 2002). Nakrem et al's (2012) study showed that the nursing home itself is not associated with home; when residents talked about 'going home' they meant their own room and not the nursing home itself.…”
Section: Public and Private Spacementioning
confidence: 97%
See 2 more Smart Citations
“…Activities that are regarded as private do not always occur away from other people's gaze (Solove, 2002). Nakrem et al's (2012) study showed that the nursing home itself is not associated with home; when residents talked about 'going home' they meant their own room and not the nursing home itself.…”
Section: Public and Private Spacementioning
confidence: 97%
“…However, the institutional routines that were task-and scheduled-oriented, rather than person-oriented, hindered residents from achieving this and made them less independent. Residents who needed help getting up in the morning and into bed in the evening, in particular, were dependent on the staff's routines (Nakrem et al, 2012).…”
Section: Block Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Overgang til institusjonell omsorg kan vaere preget av sterke følelser som skyld, usikkerhet, skam og fortvilelse O'Shea, Weathers, & McCarthy, 2014). Det er viktig for både beboere og pårørende å skape et «privat hjem» på sykehjemmet slik at beboernes personlige vaner kan lede institusjonelle rutiner og støtte meningsfylte aktiviteter (Nakrem, Vinsnes, Harkless, Paulsen, & Seim, 2012;O'Shea et al, 2014).…”
Section: Referee* Introduksjonunclassified
“…Nursing homes are ambiguous environments, combining elements of home with institutional routines, and as such may still retain elements of institutional living (Hauge and Kristin 2008;Nakrem et al 2013). As a nursing home can be a home for a couple, more systematic research is needed on couples' experiences of everyday family life in the nursing home, the intersection of formal and informal care when the spouse is a coresident, and staff relations and responsibilities to the cohabiting spouse.…”
Section: Introductionmentioning
confidence: 99%